Development of a Fuzzy Analysis System for Optimization and Evaluation of Production Costs in the Automotive Industry - Feizollahi, Sadegh; Mansouri, Bahman; Ahmadi, Vahid (Management Strategies and Engineering Sciences, 2026)
The present study aims to develop a model for evaluating the efficiency of production costs in Iranian automotive manufacturing companies using a fuzzy analysis system. The research methodology is a mixed-methods approach in which, in the qualitative phase, interviews with experts led to the extraction of 17 key variables, and in the quantitative phase, a fuzzy expert inference system was employed for model construction. Based on input data collected from four major Iranian automotive manufacturers, the results indicate that the production cost efficiency of these companies is at a moderate level or below. According to the model outputs derived from the defined inference rules, the highest level of production cost efficiency belongs to the second company; however, it is noteworthy that even this company’s cost efficiency remains only at a moderate level. This finding suggests that overall production cost efficiency in the Iranian automotive industry is generally low, with the maximum observed efficiency merely reaching a moderate level. The first company ranks next with moderate efficiency, followed by the third and fourth companies, whose production cost efficiency levels fall below the moderate threshold. Given that production cost efficiency is directly related to productivity, and productivity is inversely related to the final cost of products, the findings of this study clearly demonstrate these relationships within the context of Iran’s automotive industry. The relatively low production cost efficiency observed in these companies—ranging from moderate to below moderate—constitutes one of the primary factors contributing to the high prices of their manufactured products.